Lowering the transmission and spread of human coronavirus. Issue 3 (5th October 2020) - Meyers, Craig; Robison, Richard; Milici, Janice; Alam, Samina; Quillen, David; Goldenberg, David; Kass, Rena
Abstract: The emergence of the severe acute respiratory syndrome coronavirus 2 pandemic has created an unprecedented healthcare, social, and economic disaster. Wearing of masks and social distancing can significantly decrease transmission and spread, however, due to circumstances such as medical or dental intervention and personal choice these practices have not been universally adopted. Additional strategies are required to lessen transmission. Nasal rinses and mouthwashes, which directly impact the major sites of reception and transmission of human coronaviruses (HCoV), may provide an additional level of protection against the virus. Common over‐the‐counter nasal rinses and mouthwashes/gargles were tested for their ability to inactivate high concentrations of HCoV using contact times of 30 s, 1 min, and 2 min. Reductions in titers were measured by using the tissue culture infectious dose 50 (TCID50 ) assay. A 1% baby shampoo nasal rinse solution inactivated HCoV greater than 99.9% with a 2‐min contact time. Several over‐the‐counter mouthwash/gargle products including Listerine and Listerine‐like products were highly effective at inactivating infectious virus with greater than 99.9% even with a 30‐s contact time. In the current manuscript we have demonstrated that several commonly available healthcare products have significant virucidal properties with respect to HCoV.